A GPGPU-accelerated implementation of groundwater flow model in unconfined aquifers for heterogeneous and anisotropic media. (March 2018) - Carlotto, T.; da Silva, R.V.; Grzybowski, J.M.V.
Abstract: The application of computer simulation models plays a significant role in the understanding of water dynamics in basins. The recent and explosive growth of the processing capabilities of General-Purpose Graphics Processing Units (GPGPUs) has resulted in widespread interest in parallel computing from the modelling community. In this paper, we present a GPGPU implementation of finite-differences solution of the equations of the 2D groundwater flow in unconfined aquifers for heterogeneous and anisotropic media. We show that the GPGPU-accelerated solution implemented using CUDA 1 C/C++ largely outperforms the corresponding serial solution in C/C++. The results show that the GPGPU-accelerated implementation is capable of providing up to a 56-fold speedup in the solution using an ordinary office computer equipped with an inexpensive GPU 2 card. The code developed for this research is available for download and use athttp://modelagemambientaluffs.blogspot.com.br/ . Highlights: The model solves groundwater flow in unconfined aquifers with moving.boundary. The model is easily tailored to be coupled to an overland flow model. The GPGPU-accelerated implementation provides over 50-fold speedup. Transient solutions in grids with 5 million points obtained in about 5 min. Our high-performance implementation is open-source.